Design, construction and experimental study of electric cum solar oven-II - Nandwani, Shyman S. (1989)
As in many developing countries,35-401 of the population of Costa Rica still use firewood for domestic cooking.Considering the fact that Costa Rica is blessed with good sunshine,good hydroelectric potential,and there exist good electric network,a hybrid solar oven was thought to be useful.In the present paper the construction and working of new type of Electric Cum Solar Oven(ECSO) has been described.This oven can be used for cooking and baking any type of meal at any time during the year employing solar and/or electric energy but consuming the minimum quantity of electric energy in case it is required.